Avoiding rather than resisting herbivore attacks is often the first line of plant defence. (25th September 2021) - Lev-Yadun, Simcha
Abstract: A common idea is that resisting or blocking herbivore attacks by structural, chemical and molecular means after they have commenced is the first line of plant defence. However, these are all secondary defences, operating only when all the various methods of avoiding attack have failed. The real first line of plant defence from herbivory and herbivore-transmitted pathogens is avoiding such attacks altogether. Several visual, chemical and 'statistical' methods (and commonly their combined effects) have been proposed to allow avoidance of herbivore attacks. The visual types are camouflage, masquerade, aposematic coloration of toxic or physically defended plants (including Müllerian/Batesian mimicry), undermining herbivorous insect camouflage, delayed greening, dazzle and trickery coloration, heterophylly that undermines host identification, leaf movements, and signalling that colourful autumn leaves are soon to be shed. The mimicry types include: herbivore damage, insects and other animals, fungal infestation, dead/dry leaves or branches, animal droppings, and stones and soil. Olfactory-based tactics include odour aposematism by poisonous plants, various repelling volatiles, mimicry of faeces and carrion odours, and mimicry of aphid alarm pheromones. The 'statistical' methods are mast fruiting, flowering only once in many years and being rare. In addition to the theoretical aspects, understanding these mechanisms may have considerable potential for agricultural or forestry applications.